Childhood glaucoma profile in a Southwestern Ethiopia tertiary care center: a retrospective study - Mulugeta, Tarekegn; Gebremichael, Guteta; Adugna, Sufa (BMC ophthalmology, 2024)
Background Childhood glaucoma is a major cause of childhood blindness worldwide. The profile of childhood glaucoma has not been well characterized in sub-Saharan Africa. Thus, this study was designed to describe demographics, clinical features, managements of childhood glaucoma, and improvements in visual acuity (VA) and intraocular pressure (IOP) from baseline to final visit. Methods This retrospective study included glaucoma patients below 18 years old who were diagnosed between September 2019 to August 2022. Childhood glaucoma diagnosis and classification was made as per the Childhood Glaucoma Research Network Classification (CGRN). Results A total of 105 children (181 eyes) were diagnosed with glaucoma. The most common type of childhood glaucoma was primary congenital glaucoma (PCG) constituting (42%, n = 76 eyes, 95% confidence interval (CI), 34.7–49.5%; P = 0.037), followed by glaucoma suspect (22.1%, n = 40 eyes, 95% CI, 16.3–28.9%; P < 0.001) and juvenile open-angle glaucoma (JOAG) (15.5%, n = 28 eyes, 95% CI, 10.5–21.6%; P < 0.001). While the most common type of secondary glaucoma was steroid-induced glaucoma, followed by glaucoma following cataract surgery. Bilateral glaucoma was found in 72.4% ( n = 76 children, 95% CI, 62.8–80.7%; P < 0.001) of children. In both primary and secondary glaucoma, boys were affected more than girls, in ratio of 2:1 and 2.7:1, respectively. The mean age at presentation for patients with PCG was 2.7 years. Close to 93.4% (71) of PCG eyes were managed surgically, of which majority underwent combined trabeculotomy and trabeculectomy (CTT). Most of secondary glaucoma cases were treated medically. Overall, 85.3% (111) of eyes had successful control of IOP ≤ 21 mmHg. Conclusion PCG was the most common type of childhood glaucoma. One of a well-recognized challenge in developing countries, late presentation of patients with PCG, was also observed in our study. Which highlights, the need of increasing access to eye-care service and awareness of childhood glaucoma as a major public health issue. Steroid-induced glaucoma was the most common type of secondary glaucoma; appropriate measures should be taken to prevent this preventable glaucoma.